Influence of diuretic-induced dehydration on competitive sprint and power performance - Watson, G.; Judelson, D. A.; Armstrong, L. E.; Yeargin, S. W.; Casa, D. J.; Maresh, C. M. (Medicine & Science in Sports & Exercise, 2005)
Diuretic-induced dehydration impairs prolonged running performance (> 1500 m). Sprinting performance may suffer by similar mechanisms (i.e., altered cardiovascular strain, heat storage, and metabolism) or may improve because of reduced mass to accelerate and carry.